Chlorella vulgaris-supplemented Diet Enhances Growth, Immunity, and Survival in Red Hybrid Tilapia - Aslah Mohamad; Syafiq-Aizat Hamid; Mohamad Azzam-Sayuti; Khozirah Shaari; Annas Salleh; Muhammad Farhan Nazarudin; Woro Hastuti Satyantini; Ina Salwany Md Yasin (Faculty of Fisheries and Marine Universitas Airlangga, 2026)
Graphical Abstract Highlight Research 1. Dietary supplementation with Chlorella vulgaris at 2.5% significantly enhanced tilapia growth rate, final body weight, and feed conversion ratio. 2. Tilapia fed with the C. vulgaris-enriched diet showed higher survival rates following bacterial challenges with Streptococcus agalactiae and Aeromonas hydrophila. 3. C. vulgaris-enriched diet upregulated the expression of key immune-related genes (MHC-I, MHC-II, C-type lysozyme, TNF-α, and IL-1β), indicating activation of both innate and adaptive immune responses. 4. Microalgae, C. vulgaris, functions as both a growth promoter and immunostimulant in tilapia, offering a sustainable, antibiotic-free strategy to enhance fish health and productivity in aquaculture. Abstract Microalgae are increasingly explored as feed additives in aquaculture due to their potential benefits for fish health. This study evaluated the effects of a microalgae, Chlorella vulgaris-supplemented diet on the growth performance, immune-related gene expression, histopathology, and protective efficacy of red hybrid tilapia (Oreochromis sp.) following intraperitoneal injection with Streptococcus agalactiae and Aeromonas hydrophila. A total of 330 red hybrid tilapia, Oreochromis sp. were assigned to two groups: a control group fed a commercial diet (Group 1) and a treatment group receiving a diet supplemented with 2.5% C. vulgaris (Group 2) for seven weeks. Fish in the treatment group exhibited significantly higher growth rates than those in the control group. Moreover, the relative percentage survival (RPS) post-infection with S. agalactiae and A. hydrophila was 68.89 ± 1.52% and 88.89 ± 3.00%, respectively, significantly higher than in the control group (28.89 ± 0.57% and 40.00 ± 1.00%, respectively). Notably, fish fed the microalgae-supplemented diet displayed a higher expression of immune-related genes and exhibited reduced lesion severity across examined organs, indicating enhanced resistance to infection. These findings show that dietary C. vulgaris improves growth, boosts immune function, and enhances disease resistance in red hybrid tilapia, supporting its use as a sustainable functional feed ingredient. This highlights strong potential for commercial adoption, and future research should refine optimal inclusion levels and evaluate performance under real farm conditions.